Use f(x) = 5x − 2 and g(x) = 3 − x2 to evaluate the expression. (a) (f c

Algebra
Tutor: None Selected Time limit: 1 Day

Use 
f(x) = 5x − 2
 and 
g(x) = 3 − x2
 to evaluate the expression.
(a)    
(f  g)(−2)

 

(b)    
(g  f)(−2)

Jun 30th, 2015

Thank you for the opportunity to help you with your question!

f(x)=5x-2

g(x)=3-x^2

(f g) (-2) =f[g(-2])

              =f(3-(-2)^2)

              =f(3-4)

             =f(-1)

             =-5-2

             =-7


(g f) (-2)=g[f(-2]

              =g[-12]

              =3-(-12)^2

              =3-144

              =-141

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 30th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 30th, 2015
...
Jun 30th, 2015
May 29th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer